Influence of CYP2C19 functional polymorphism on Helicobacter pylori eradication - Burhan ÖZDİL and Hikmet AKKIZ and Süleyman BAYRAM and Aynur BEKAR and Ersin AKGÖLLÜ and Macit SANDIKÇI (Turkish Journal of Gastroenterology, 2019)
-